Department Leaders as Critical Conduits for the Advancement of Gender Equity Programs. Issue 1 (2nd January 2022) - Hughes, Bryce E.; Smith, Jessi L.; Bruun, Megan; Shanahan, Elizabeth A.; Rushing, Sara; Intemann, Kristen; Handley, Ian M.; Belou, Rebecca; Stoop, Chatanika; Sterman, Leila
Abstract : Although women have made tremendous strides toward gender equity within science, technology, engineering, and mathematics (STEM) fields over the past couple of decades, reaching full equity will require the support of faculty colleagues. Department chairs and heads are crucial as the conduit between administration and faculty, yet they are traditionally an understudied contingent. Through in-depth, semi-structured interviews with 10 STEM department heads at a U.S. university, we uncovered the limiting ideologies that guide department leaders' sensemaking around achieving gender equity—specifically meritocracy, objectivity, and neoliberalism. We discuss the implications for gender equity programs within higher education in terms of addressing these deeper frames of reference to achieve long-lasting outcomes. On one hand, change agents can leverage these dominant ideologies to create a shift in department leaders' mind-sets, leading to earlier understanding and buy-in; on the other hand, failing to critically challenge these deep-seated assumptions and beliefs can impede long-term success.